Physical activity, health-related quality of life and depression during pregnancy - Iva Tendais; Bárbara Figueiredo; Jorge Mota; Ana Conde
This study examines physical activity patterns among women, from pre-pregnancy to the second trimester of pregnancy, and the relationship between physical activity status based on physical activity guidelines and health-related quality of life (HRQoL) and depression over pregnancy. 56 healthy pregnant women self-reported physical activity, HRQoL and depression at 10-15 and 19-24 weeks of pregnancy and physical activity before pregnancy. Whereas vigorous leisure physical activity decreased after conception, moderate leisure physical activity and work related physical activity remained stable over time. The prevalence of recommended physical activity was 39.3% and 12.5% in the 1st and 2nd trimesters of pregnancy respectively, and 14.3% pre-pregnancy. From the 1st to the 2nd pregnancy trimester, most physical HRQoL dimensions scores decreased and only mental component increased, independently of physical activity status. No changes in mean depression scores were observed. These data suggest that physical activity patterns change with pregnancy and that physical and mental components are differentially affected by pregnancy course, independently of physical activity status.